Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Perusahaan Pada PT Kimia Farma (Persero) Tbk Periode 2016-2020 (Berdasarkan Keputusan Menteri BUMN Nomor : KEP-100/MBU/2002) - Qq Junita Putri; Elfina O. P. Damanik; Fariaman Purba (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The company's health level shows the company's financial performance. Assessment of financial performance in private companies and state-owned companies is very necessary in order to survive and develop business activities. In State-Owned Enterprises (BUMN) the financial performance assessment has regulations regulated by the Decree of the Minister of Finance Number: KEP-100/MBU/2002. This research used a quantitative descriptive method with the type of data used is secondary data in the form of financial statements and the technique used is documentation and literature study. This research used eight indicators, namely Return on Equity, Return on Investment, Cash Ratio, Current Ratio, Collection Periods, Inventory Turnover, Total Own Capital to Total Assets, Total Asset Turn Over based on the Decree of the Minister of Finance. The results of the research on the health level of PT Kimia Farma obtained a healthy predicate with the AA category in 2016 and 2017. In 2018 PT Kimia Farma obtained the Healthy predicate with the AAA category, in 2019 the healthy predicate with the A category, and the unhealthy predicate with the BB category in 2020.